2007
DOI: 10.1038/sj.cgt.7701082
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of drug resistance of hepatocellular carcinoma cells by adenoviral delivery of anti-ABCC2 antisense constructs

Abstract: Human cancers are characterized by a high degree of drug resistance. The multidrug resistance transporters MDR1-P-glycoprotein (ABCB1) and ABCC2 (MRP2) are expressed in a variety of human cancers, including hepatocellular carcinoma (HCC). The ABCC2 gene encodes a membrane protein involved in the ATP-dependent transport of conjugates of lipophilic substances. In this study we analyzed the effect of an ABCC2 antisense construct on the chemosensitization of HepG2 cells. Adenoviral vectors were constructed to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Chloromethylfluorescein reacts with intracellular glutathione to form glutathione methylfluorescein. Calcein, doxorubicin, CDF, and glutathione methylfluorescein are substrates of MRP2 (Evers et al, 2000;Tian et al, 2004;Folmer et al, 2007;Förster et al, 2008). After the loading period, the transport buffer was aspirated, and the cells were rinsed 3ϫ (200 l each) with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloromethylfluorescein reacts with intracellular glutathione to form glutathione methylfluorescein. Calcein, doxorubicin, CDF, and glutathione methylfluorescein are substrates of MRP2 (Evers et al, 2000;Tian et al, 2004;Folmer et al, 2007;Förster et al, 2008). After the loading period, the transport buffer was aspirated, and the cells were rinsed 3ϫ (200 l each) with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…These include vincristine, etoposide, cisplatin, and doxorubicin, used to treat retinoblastoma, and methotrexate and piroxicam, used to treat uveitis (Hooijberg et al, 1999;El-Sheikh et al, 2007;Folmer et al, 2007). MRP2 is an ATP-dependent efflux transporter that shifts, in addition to many therapeutic drugs, endogenous metabolites, such as estradiol 17␤-D-glucuronide, and environmental toxins, such as ochratoxin A (van Aubel et al, 1998;Leier et al, 2000).…”
mentioning
confidence: 99%
“…Multidrug resistance (MDR) to chemotherapeutic agents plays a major role in the failure of cancer therapy [5] . MDR phenotype, an intrinsic or acquired cross-resistance to a variety of structurally and functionally unrelated drugs, is almost constantly expressed in HCC and represents one of the major problems in cancer eradication by limiting the efficacy of chemotherapy [6] . Resistance to therapy can result from decreased drug uptake, increased DNA repair or drug inactivation [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, half of the tumor samples showed MRP2 overexpression, irrespective of administration of cisplatin (Table III). Since HCCs often produce bile, the intrinsic expression of MRP2 in HCC may partly explain their low sensitivity to some MRP2-dependent anti-cancer agents including cisplatin, doxorubicin, etoposide, and vincristine (7,28). Bonin et al documented that MRP2 mRNA expression level significantly increases in HCC compared to non-neoplastic liver tissue (14).…”
Section: Discussionmentioning
confidence: 99%